2020
DOI: 10.1111/acer.14433
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic and Neuroprotective Effects of Alcohol–Antioxidant Treatment on Blood–Brain Barrier Endothelial Cells

Abstract: Background: Alcohol (EtOH) is reported to adversely affect one of the most crucial roles of the blood-brain barrier (BBB), the regulation of its permeability, thereby compromising the stability of the homeostatic environment of the brain. The central component of the BBB, endothelial cells (ECs), regulates BBB transcellular transport, while their paracellular pathways are made virtually impermeable by molecular structures called tight junctions (TJs). These TJs are composed of proteins, such as claudin-5, a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…HUVECs were seeded at a density of 4 × 10 4 per well in 24‐well plates and incubated with 5‐, 10‐, 25‐, 50‐, or 100‐mM ethanol (purchased from Sigma‐Aldrich, USA). The highest concentration (100 mM) is comparable with previous in vitro studies (Boncler, Lukasiak, Dastych, Golanski & Watala, 2019; Fisher, Thomas & Abdul‐Rasool, 2020; Mishra, Agas, Schuetz, Kalluru & Haorah, 2020; Xue et al, 2018). Assuming the highest ethanol consumption as 9.8 L per year (World Health Organisation, 2018) and blood volume of adults as 5 L, the ethanol level in blood every day is approximately 92 mM, close to the highest concentration used in this study.…”
Section: Methodssupporting
confidence: 87%
See 2 more Smart Citations
“…HUVECs were seeded at a density of 4 × 10 4 per well in 24‐well plates and incubated with 5‐, 10‐, 25‐, 50‐, or 100‐mM ethanol (purchased from Sigma‐Aldrich, USA). The highest concentration (100 mM) is comparable with previous in vitro studies (Boncler, Lukasiak, Dastych, Golanski & Watala, 2019; Fisher, Thomas & Abdul‐Rasool, 2020; Mishra, Agas, Schuetz, Kalluru & Haorah, 2020; Xue et al, 2018). Assuming the highest ethanol consumption as 9.8 L per year (World Health Organisation, 2018) and blood volume of adults as 5 L, the ethanol level in blood every day is approximately 92 mM, close to the highest concentration used in this study.…”
Section: Methodssupporting
confidence: 87%
“…We used two concentrations. The concentration of 50 mM has been used in previous toxicological studies (Boncler, Lukasiak, Dastych, Golanski & Watala, 2019; Devall et al, 2020; Fisher, Thomas & Abdul‐Rasool, 2020; Mishra, Agas, Schuetz, Kalluru & Haorah, 2020; Xue et al, 2018; Zhu et al, 2017) and could be reached after daily consumption of ethanol according to the calculation described in Section 2. A much lower concentration 5 mM was also used, because researchers suggested that low levels of ethanol could induce hormesis (Calabrese & Baldwin, 2003; Hayes, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Fisher et al (2020) reported protective effects of an aspalathin-rich rooibos tincture in an in vitro BBB model. Notably this study utilised bEnd5 cells, which do not express the TJP occludin [62]. In our study, an ethanol extract of green rooibos decreased the total occludin signal significantly under baseline conditions (absence of TA treatment), which, in the context of the report from Fisher et al (2020), suggests more than one potential mechanism of action for rooibos-related beneficial modulation of tightjunction barriers.…”
Section: Discussionsupporting
confidence: 67%
“…Although rooibos is anecdotally acclaimed for its calming effect few studies have investigated the effect of rooibos on the brain and nervous system and associated behavioural outcomes. Somewhat disappointingly, most in vitro studies in this context–albeit with positive results–seem largely focused on antioxidant effects ( Hong et al, 2014 ; Fisher et al, 2020 ; Ma et al, 2020 ; Lopez et al, 2022 ; Brasil et al, 2023 ). Only two of these expanded their investigation and also reported different modulatory mechanisms in the context of serotonin metabolism ( Hong et al, 2014 ; Lopez et al, 2022 ), which provides some additional mechanistic support for an anxiolytic or calming effect.…”
Section: Rooibos: Doomed To Fail or On The Road To Success?mentioning
confidence: 99%